The Effect of Workload, Work Relationships, and Work Facilities on Employee Productivity at PT JNE Medan Main Branch - Risnaini Risnaini; Emi Wakhyuni (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the effect of workload, work relationships, and work facilities on employee productivity at PT JNE Medan Main Branch. The population in this study includes all permanent employees totaling 50 people, who are also used as samples using the saturated sampling method. The study was conducted in 2025. Data were obtained through distributing questionnaires as primary-quantitative data collection instruments and analyzed using multiple linear regression through SPSS version 24. The findings show that the three independent variables, both individually and simultaneously, have a positive and significant effect on work productivity. The results of the t-test show that workload has a regression coefficient of 0.324 (tcount = 3.631; sig. = 0.001), work relationships of 0.238 (tcount = 2.373; sig. = 0.022), and work facilities of 0.492 (tcount = 3.715; sig. = 0.001). The F test obtained an F count of 210.961 (sig. = 0.000), exceeding the F table of 2.807. The R value of 0.966 indicates a very strong relationship between the three variables and work productivity. Work facilities are recorded as the most dominant variable with the highest beta value, which is 0.400. As much as 92.8% of the variation in work productivity is explained by these three variables, while the rest is influenced by other factors.